Effects of Kumo Teaching Strategy on Students’ Achievement in Electrical/Electronics in Technical Colleges in Niger State - G.A., Usman; Hassan, Abdullahi Muhammad; M.M, Bala (Asian Journal of Interdisciplinary Research, 2020)
The study investigated the effects of kumon teaching strategy methods on students’ achievement in electrical/electronic in technical colleges in Niger State. The study adopted a pretest-posttest quasi-experimental design with non-equivalent control group. The sample for the study consisted of 122 technical college III electrical/electronic students. Purposive sampling was used to select four schools in Minna education zone. The instrument used for the study is the Electrical/Electronic Achievement Test (EAT) designed by the researcher. Section A of the instrument contained 20 multiple-choice items, section B contained 2 essay questions all for the measurement of students’ achievement in electrical/electronic. Four research questions and four hypotheses were formulated to guide the study. The hypotheses were tested at 0.05 level of significance. The data collected were analyzed using mean and standard deviation and ANCOVA statistical tools. The results showed that ability level of students significantly influence achievement in electrical/electronic. The high ability students outperformed their medium and low ability students. Gender was not a significant factor. The interaction effect of gender and method was not statistically significant. There was a significant difference in the mean achievement scores of students taught electrical/electronic using problem-solving and those taught using discussion teaching methods. Finally it was recommended that teachers of electrical/electronic should adopt the use of kumon teaching strategy. This will go a long way in improving problem-solving skills of students no matter their ability level.